Fishing for influence: Fisheries science and evidence in water resources development in the Mekong basin - Richard M. Friend (2018)
During the last decade there has been a concerted effort in the Mekong basin to research the capture fisheries in an attempt to influence national and regional water resource policy and practice, particularly hydropower development. As a result of this research effort, the Mekong capture fisheries are better documented than ever before. There is broad consensus on the key conclusions of this research - on the scale and value of production, its importance to local livelihoods, and the ecological drivers of the natural productivity. Despite this research success the agendas of water resources management have not changed, and the pace of hydropower development has accelerated. This presents a dilemma for fisheries science and research in its efforts to influence policy. This paper considers the models and assumptions of policy influence that have underpinned this fisheries research effort, and presents alternative approaches for fisheries science to better engage in influencing policy. The paper argues that addressing the neglect of capture fisheries in the Mekong is fundamentally a governance challenge of setting development values and pathways. Meeting such a challenge, in the context of the Mekong, requires a democratising and civic science that broadens the decision-making arena as much as it produces new evidence and arguments.